2015
DOI: 10.5027/andgeov43n1-a01
|View full text |Cite
|
Sign up to set email alerts
|

Holocene tephrochronology around Cochrane (~47° S), southern Chile

Abstract: ABSTRACT. Two Holocene tephras encountered in outcrops, cores and trenches in bogs, and lake cores in the area around Cochrane, southern Chile, are identified (based on their age, tephra glass color and morphology, mineralogy, and both bulk and glass chemistry) as H1 derived from Hudson volcano, and MEN1 derived from Mentolat volcano. New AMS radiocarbon ages indicate systematic differences between those determined in lake cores (MEN1=7,689 and H1=8,440 cal yrs BP) and surface deposits (MEN1=7,471 and H1=7,891… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(106 citation statements)
references
References 36 publications
(66 reference statements)
9
83
0
Order By: Relevance
“…Although, there is still not enough spatial coverage to constrain isopach maps for the eruptions that produced all the tephra, some of these tephra do appear to correspond chronologically and petrochemically to some of the larger eruptions identified previously by Stern (1998, 2004), Mella et al (2012), Stern et al (2013) and Weller et al (2014), while others occurred at times when no such large eruption has been previously identified. Tephras 'a' in the two cores may correspond to Late-Holocene eruption MEL2 of Melimoyu (Table 1) previously documented by Naranjo and Stern (2004).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Although, there is still not enough spatial coverage to constrain isopach maps for the eruptions that produced all the tephra, some of these tephra do appear to correspond chronologically and petrochemically to some of the larger eruptions identified previously by Stern (1998, 2004), Mella et al (2012), Stern et al (2013) and Weller et al (2014), while others occurred at times when no such large eruption has been previously identified. Tephras 'a' in the two cores may correspond to Late-Holocene eruption MEL2 of Melimoyu (Table 1) previously documented by Naranjo and Stern (2004).…”
Section: Discussionmentioning
confidence: 88%
“…Tephra 'b' in Mallín El Embudo and 'f' in Lago Shaman do not result from the H2 eruption of Hudson as previously suggested (de Porras et al, 2012(de Porras et al, , 2014, but rather from a mid-Holocene eruption of the Melimoyu volcano not previously described. Tephras 'i' from the Lago Shaman core and 'h' from the Mallín El Embudo core may have been deposited during the mid-Holocene MEN1 eruption of Mentolat (Table 1; Naranjo and Stern, 2004;Stern et al, 2013). Tephra 'v' in Lago Shaman was produced by the Late-Glacial Ho eruption of Hudson (Table 1; Weller et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tephra layer at 268-274 cm is geochemically fingerprinted to the large eruption of Volcán Hudson (H1) Stern, 1998, 2004;Prieto et al, 2013;Stern et al, 2016). The maximum age for H1 of 7241 ± 23 14 C yr BP used here (Stern et al, 2016) is older than that of 6890 ± 100 14 C yr BP, given by Prieto et al (2013), but, as a similar exercise for the Volcán Reclus R1 layer has demonstrated, improved accuracy may be achieved by selecting ages from higher-resolution sediment and peat cores (McCulloch Table 2.…”
Section: Chronologymentioning
confidence: 99%